1993
DOI: 10.1111/j.1439-0434.1993.tb01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Cut Rose Flower Cultivars to Infections by Different Isolates of Botrytis cinerea

Abstract: A method was developed for the inoculation of flowers of cut roses with conidia of Botrytis cinerea. Flower buds were inoculated by spraying of conidial supensions that were ultrasonicated for 10 s. The differences in susceptibility between 8 rose cvs to infections of isolate Bc‐33 and the differences in pathogenicity between 14 5. cinerea isolates to cv. ‘Sonia’ were evaluated. Isolates obtained from rose flowers caused higher infection rates than those obtamed from various other hosts. The CVS ‘Madelon’, ‘Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Since the fungal isolate used in this study was obtained from cannabis plants, it might be interesting to test if isolates from other plants would elicit SAR in cannabis. A similar hypothesis was confirmed in rose (Pie and Brouwer, 1993) and grapevine (Derckel et al, 1999) where B. cinerea isolates were more virulent on the plant species that they originated from than isolates obtained from other plant species.…”
Section: Lack Of Sar-mediated Elicitation Of Defense Genes Expressionsupporting
confidence: 60%
“…Since the fungal isolate used in this study was obtained from cannabis plants, it might be interesting to test if isolates from other plants would elicit SAR in cannabis. A similar hypothesis was confirmed in rose (Pie and Brouwer, 1993) and grapevine (Derckel et al, 1999) where B. cinerea isolates were more virulent on the plant species that they originated from than isolates obtained from other plant species.…”
Section: Lack Of Sar-mediated Elicitation Of Defense Genes Expressionsupporting
confidence: 60%
“…For example, strains isolated from tomato were more aggressive on tomato leaves than strains isolated from grapevine (Cotoras & Silva, 2005) and strains collected on grapevine were more aggressive on this plant than strains from other host plants (Derckel et al, 1999). Pie & Brouwer (1993) also reported that strains of B. cinerea collected on roses had higher aggressiveness on rose petals than strains collected on gerbera flowers or pea leaves. Such differences in aggressiveness may provide a limitation in gene flow among strains of the pathogen present on different hosts, as successive generations of inoculum (possibly numerous in one growing season, depending on the crop) result in the gradual selection of the most aggressive strains (Decognet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Damage caused by Botrytis cinerea has long been one of the floral industry's most significant postharvest challenges (Coyier 1985, Droby andLichter 2007), and cut rose cultivars differ in Botrytis susceptibility (Pie andBrouwer 1993, Hammer andEvensen 1994). Ethylene (ET) exposure can also be problematic for sensitive species and cultivars of cut flowers during postharvest handling, and roses are known to be slightly to moderately sensitive to ET across cultivars (Dole et al 2017) with demonstrated sensitivity differences among cultivars (Reid et al 1989, Macnish et al 2010.…”
Section: Introductionmentioning
confidence: 99%